Bacteria-targeted biomaterials: Glycan-coated microspheres to bind Helicobacter pylori. (15th March 2016) - Gonçalves, Inês C.; Magalhães, Ana; Costa, Ana M.S.; Oliveira, José R.; Henriques, Patrícia C.; Gomes, Paula; Reis, Celso A.; Martins, M. Cristina L.
Graphical abstract: Abstract: Gastric cancer is the third leading cause of cancer related deaths worldwide and Helicobacter pylori ( H. pylori ) persistent infection has been pointed as a causative agent of this disease. Current antibiotic based treatments to eradicate this bacterium fail in 20% of the patients, potentially leaving 140 million people in the world without alternative therapy. It is herein proposed the use of azide–alkyne coupling ("click chemistry") to produce glycan-coated mucoadhesive microspheres that bind and remove the H. pylori adherent to the gastric mucosa through specific bacterial adhesin–glycan interactions. Glycan immobilization is performed via chitosan's primary alcohol group, rather than the more reactive primary amines in order to preserve the amine groups that confer chitosan its mucoadhesiveness. It is shown that chitosan microspheres decorated with Lewis b glycans (Leb-Mic) bind specifically to H. pylori strains expressing the BabA adhesin (strains recognized as highly pathogenic) (∼230 bacteria/microsphere), are non-cytotoxic, are retained in the stomach of C57BL/6 mice for around 1.5 h. Also, these Leb-Mic are able to prevent and remove H. pylori adhesion to gastric mucosa expressing the same glycan, in tissue sections from mice and human gastric mucosa ( in vitro ) and in fresh mice stomachs ( ex vivo ). These results provide proof-of-concept on the potential of glycan-decorated microspheres as an innovative therapeutic strategy against H. pylori and highlight the prospective of using targeted biomaterials to fight gastrointestinal infection. Statement of Significance: Gastric cancer has been associated with persistent infection by Helicobacter pylori, a bacterium that colonizes half of world population and whose available antibiotic treatment fails in 20% of cases. H. pylori adhesion to gastric epithelium is mediated between bacterial adhesins and glycans expressed in gastric mucosa. We demonstrate that these glycans can be immobilized in a controlled orientation into mucoadhesive chitosan microspheres, making them selective for different H. pylori strains. Efficacy studies (in vitro and ex vivo) with mice and human gastric mucosa that express the same glycan, revealed microspheres capacity to remove/prevent specific H. pylori adhesion, envisaging their future application as bacteria scavenging from stomach. This bacteria-binding strategy can be extrapolated to target other cells/bacteria using suitable ligands.